Collaborative Governance in Overcoming Tuberculosis Cases in the Riau Islands Province - Talaallayna, Nonie; Winarti, Novi (Yayasan Ilomata, 2024)
Riau Islands is one of the provinces that handles TB cases by carrying out a collaborative process, which is stated in the Decree of the Riau Islands Province Tuberculosis Management Acceleration Team in 2022. This research aims to find out the collaboration process carried out by stakeholders involved in tackling TB cases in Islands Province Riau. This research uses a qualitative approach. by presenting the results descriptively, what is used is qualitative data analysis, namely data reduction, data display and conclusion drawing/verification to present the findings in a structured manner. Then the results are described based on the dynamics of collaborative governance according to Ansell and Gash, which uses five indicators, namely face to face, trust building, commitment to process, shared understanding, intermediated outcomes. The research results, the collaboration has been reduction the TB cases in the Riau Islands province, but this is not significant when compared to the target to be achieved. Apart from that, there are still cases that have not been reported by Health Service Facilities to the Tuberculosis Information System. So future changes or revisions regarding collaboration are still needed to make it easier to handle the obstacles faced by stakeholders.